Associations of parecoxib and other variables with recovery and safety outcomes in total knee arthroplasty: insights from a retrospective cohort study - Hu, Ching-Yuan; Wang, Jen-Hung; Chen, Tsung-Ying; Wang, Po-Kai (Frontiers in Surgery, 2024)
Background: Early mobilization post-total knee arthroplasty (TKA) significantly affects patient outcomes. While parecoxib is known to reduce postoperative pain and morphine use with a favorable safety profile, its impact on mobilization timing post-TKA remains uncertain. This retrospective study aims to assess parecoxib's influence on postoperative mobilization timing in TKA patients without compromising safety. Methods: This study included unilateral TKA patients treated for primary knee osteoarthritis under general anesthesia. We divided the study period into two intervals, 2007-2012 and 2013-2018, to evaluate temporal differences. Both the control group and parecoxib group received standard postoperative oral analgesics and as-needed intramuscular morphine. The control group did not receive parecoxib, while the parecoxib group did. Primary outcomes compared postoperative complications and mobilization timing between groups, with secondary outcomes including length of hospital stay (LOS), Visual Analog Scale (VAS) scores for pain, as-needed morphine use, and postoperative nausea/vomiting. Results: Parecoxib did not increase postoperative complications. Unmatched comparison with patients in controlled group found that patients in parecoxib group had significantly shortened mobilization time (2.2±1.1 vs. 2.7±1.6 days, P < 0.001) and LOS (6.7±2.5 vs. 7.2±2.1 days, P = 0.01). Multivariate analysis linked parecoxib use with faster mobilization (β= -0.365, P <0.001) but not LOS. Males showed increased mobilization time and LOS compared to females during the period of 2007-2018, but gender had no significant association with LOS during the period of 2013-2018. The 2013-2018 period saw significant reductions in both mobilization time and LOS. Use of a tourniquet and local infiltration analgesia showed no significant impact. ASA classification 1-2 was positively associated with faster mobilization but not LOS. Longer operation times were linked to delayed mobilization and increased LOS. Conclusion: In this study, intravenous parecoxib injection, female gender, and shorter OP time had consistent positive association with shorter time to mobilization after individual multivariate analysis in 2 different period. The use of parecoxib had consistent no significant association with LOS. Only shorter OP time was consistent positive associated with shorter LOS.